Watershed Management in Indonesia: A Regulation, Institution, and Policy Review - Andi Setyo Pambudi (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
Watershed Management as part of regional development in Indonesia is facing various complex and interrelated issues. It is indicated by the lack of integration among sectors, agencies, regions and community participation. The increasing frequency of floods, droughts, landslides, and water crisis problems recently shows that watershed management in Indonesia has not been effective yet in enhancing sustainable development. Furthermore, the damage of watersheds is commonly observed from the upstreams only, such as the addition of cultivated land area and massive settlement, so that erosion and sedimentation affect the declining productivity of land and the increasing frequency of water-related disasters. If watersheds are defined as a container of water cycle, then solving its problem by simply rehabilitating the upstreams is not completely right. Government policies on watersheds management need to be reviewed from its initial aspects of science as well, including existing regulations and institutions, so that the contribution and linkage among sectors could be visible. The concept of Integrated Watersheds Management is basically participatory management of multi-stakeholders in conservations and utilization through an ecological concept of interdependency between nature and human beings. This paper aims to explore the effectiveness of watershed management policies in Indonesia in the context of history, regulation, institutions, and policy implementation.